Feminist criminology in an era of misogyn - Chesney-Lind, Meda (Criminology, 2020)
In this address I make the case for continuing to focus criminological research on gender, sexism, and racism within our lives and within our profession. I also provide a brief case study of a topic many would feel falls well outside our field: reproductive rights. Data are reviewed to reveal the impact of gender on the lives of women—notably the devaluation of work done by women, particularly if the work is deemed feminist. Afterward, recent data on the persistence of both sexism and racism in our field are reviewed. Despite gains made by women (notably in the membership of the field), the highest positions in our professional association are held by men, particularly by White men. Data on the importance of reproductive rights to women are then considered, notably the fact that nearly one third of women will need abortion services by the time they reach middle age. Finally, I review recent efforts by conservatives to recriminalize abortion, specifically through the passage of laws making abortion difficult to arrange, or even outlawing the provision of abortion services. These efforts directly involve the criminal justice system in the criminalization of women's bodies.